2023
DOI: 10.1109/tnsre.2022.3214806
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Increasing Assistance From a Powered Prosthesis on Weight-Bearing Symmetry, Effort, and Speed During Stand-Up in Individuals With Above-Knee Amputation

Abstract: After above-knee amputation, the missing biological knee and ankle are commonly replaced with a passive prosthesis, which cannot provide net-positive energy to assist the user. During activities such as sit-to-stand, above-knee amputees must compensate for this lack of power using their upper body, intact limb, and residual limb, resulting in slower, less symmetric, and higher effort movements. Previous studies have shown that powered prostheses can improve symmetry and speed by providing positive assistive po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Sit-down and stand-up are related movements, which are both essential for independent living. In our previous study of stand-up with a powered prosthesis, we observed similar improvements in weight-bearing symmetry [ 13 ]. During stand-up the index of asymmetry was measured at an extraction point which is not present during sit-down, and so different methods of extracting IOA metrics were used.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Sit-down and stand-up are related movements, which are both essential for independent living. In our previous study of stand-up with a powered prosthesis, we observed similar improvements in weight-bearing symmetry [ 13 ]. During stand-up the index of asymmetry was measured at an extraction point which is not present during sit-down, and so different methods of extracting IOA metrics were used.…”
Section: Discussionsupporting
confidence: 71%
“…The desired knee joint position at which the peak torque was reached was set in the controller software to approximately 85% of each subject’s sitting knee angle, similar to able-bodied sit-down biomechanics [ 40 ]. The powered ankle joint was controlled using impedance control, using fixed virtual stiffness (K = 3 Nm/deg) and fixed virtual damping (B = 0.2 Nm/deg/s) similar to our previous work [ 12 , 13 ]. The ankle equilibrium position was controlled as a function of knee position (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The knee joint position at which the peak torque was reached was set at approximately 85 percent of each subject's sitting knee angle after [40]. The powered ankle joint was controlled using impedance control, using xed stiffness and damping similar to our previous work [12], [13].…”
Section: Powered Prosthesis Sit-down Controllermentioning
confidence: 99%
“…With these powered prostheses, amputees are able to perform activities such as crossing obstacles, squatting, or walking up stairs that are not possible with passive prostheses [3] [4]. Furthermore, activities that are possible with passive prostheses, such as walking, ascending ramps, sitting down, and standing up, can become more efficient with powered prostheses [5][6] [7] [8]. To obtain stable and efficient ambulation, powered prostheses need controllers capable of coordinating the actions of the prosthesis with the movement intention of the user.…”
mentioning
confidence: 99%